2019
DOI: 10.1001/jamanetworkopen.2019.7216
|View full text |Cite
|
Sign up to set email alerts
|

Association of US Medical Marijuana Laws With Nonmedical Prescription Opioid Use and Prescription Opioid Use Disorder

Abstract: Key Points Question Is enactment of medical marijuana laws in the United States associated with changes in nonmedical prescription opioid use and prescription opioid use disorder among prescription opioid users overall and by age and racial/ethnic group? Findings This cross-sectional study using individual-level restricted data from the 2004 to 2014 US National Survey on Drug Use and Health showed small increases in nonmedical prescription opioid use and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…However, the role of more permissive Cannabis legislation in the opioid crisis is not yet fully understood. One individual‐level analysis of national survey data found that medical Cannabis laws were not associated with changes in the prevalence of opioid use disorder, and in fact were associated with a small increase in opioid use [13]. At the same time, numerous ecological studies suggest that state medical and recreational Cannabis laws are associated with reductions in opioid prescriptions, opioid‐related hospitalizations and overdose deaths [14–20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of more permissive Cannabis legislation in the opioid crisis is not yet fully understood. One individual‐level analysis of national survey data found that medical Cannabis laws were not associated with changes in the prevalence of opioid use disorder, and in fact were associated with a small increase in opioid use [13]. At the same time, numerous ecological studies suggest that state medical and recreational Cannabis laws are associated with reductions in opioid prescriptions, opioid‐related hospitalizations and overdose deaths [14–20].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, numerous ecological studies suggest that state medical and recreational Cannabis laws are associated with reductions in opioid prescriptions, opioid‐related hospitalizations and overdose deaths [14–20]. Although ecological studies cannot establish causality [21], authors have drawn upon the substitution hypothesis to interpret these findings, positing that individuals may substitute Cannabis for prescription and illicit opioids, particularly to manage pain [13,15,16,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…103 Two additional studies in 2019 on medical marijuana policies found lower rates of opioid use in areas with legalized medical marijuana policy than in areas without such policy, consistent with our results. 104,105 However, a replication of the article by Bachhuber et al 78 that used more recent data concluded that associations between opioidrelated overdose mortality and cannabis laws may be "spurious": the association between opioid-related overdose mortality and medical marijuana laws reversed direction, and mortality increased during the longer time horizon, but no association was found between recreational marijuana laws and the number of overdoses. 106 Studies of prescribing guidelines and educational interventions published after our review were consistent with studies we reviewed.…”
Section: Discussionmentioning
confidence: 98%
“…Some prior studies suggest that state medical cannabis laws may be associated with reductions in opioid prescribing, opioid use disorder, and opioid overdose [8][9][10][11][12][13][14][15][16], while others suggest that medical cannabis laws may lead to increased nonmedical opioid use and overdose [17,18]. The available research is limited by five key factors, which the study described in this protocol is designed to overcome:…”
Section: Introductionmentioning
confidence: 99%